Novel Metaphors in Indonesian Political Discourse on Covid-19 Pandemic Handling - Maharsi, Eni; Suhandano, Suhandano; Udasmoro, Wening (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
Metaphor is a part of human cognition that plays an important role in human knowledge and experience. This study aims at examining novel metaphors based on the metaphorical language used by Indonesia’s state leader, President Joko Widodo, in his speeches on COVID-19 and their functions for pandemic handling and post-pandemic preparednessin Indonesia. Data were speeches produced during the first and second waves of the pandemic and taken from official website of Cabinet Secretariat of the Republic of Indonesia. The metaphors identified in the speeches were analysed using Critical Metaphor Analysis proposed by Charteris-Black (2004, 2011, 2021). The identified novel metaphors were categorized under the following seven source domains: breakfast, computer, crater, test, teacher, momentum, wheel, and fire. The identified metaphors could be classified into three types of novel metaphor: linguistic structural metaphors, metaphors with new target domains, and new mapping metaphors. Results of analysis revealed that the metaphors of examination/test, teacher, and fire were high in frequency. As for the function, those novel metaphors could be interpreted as Jokowi's way to reflect changing realities and motivate actions. Overall, the use of metaphors implied Jokowi's priority responses toward pandemic, i.e. to persuade the importance of solidarity and collectivity, strong sense of perseverance and resilience, as well as mutual cooperation. This study is expected to give insight that government leadersemploy metaphors as appropriate to situational context as the metaphors they can be effective in shaping public opinion and winning public support for health measures and policymaking in time of crises.